Evaluación del comportamiento poscosecha del tomate de mesa (lycopersicum esculentum), híbrido nemo netta, con 2 índices de cosecha, en 3 atmósferas modificadas, a 3 temperaturas de almacenamiento. Latacunga – Cotopaxi 2015 - Cando Chusín, José Miguel (2015)
The table tomato (Lycopersicum esculentum) originating in South America, has a high nutritional and medicinal value, it is very rich in lycopene, the pigment that acts as protector of cells against the effects of oxidation. In Ecuador producers lose 20 to 80% of its products after harvest, because life processes continue in vegetables after harvest, in 2013 production increased by 2% and for the 2014 and 2015 the expectations of farmers was an increase of about 6% in tomato production. The present research is focused on reducing post-harvest losses. To which an investigation was conducted at the Experimental Center of Agricultural Sciences Technical University of Cotopaxi, located in the Salache parish, Latacunga town, Cotopaxi Province at an altitude of 2,780 m.s.n.m. where factors three were assessed: Storage Temperatures modified atmospheres and indices of maturity, Plots in a Design divided twice for significance testing was used Tukey 5%. In order to achieve these objectives, the following variables were analyzed: weight, flesh firmness, Brix, disease incidence and days on the hanger. From the results, it was concluded….